2000
DOI: 10.1074/jbc.m002338200
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of T Cell Activation following Inhibition of Dipeptidyl Peptidase IV/CD26 by the N-terminal Part of the Thromboxane A2 Receptor

Abstract: Using synthetic inhibitors, it has been shown that the ectopeptidase dipeptidyl peptidase IV (DP IV) (CD26) plays an important role in the activation and proliferation of T lymphocytes. The human immunodeficiency virus-1 Tat protein, as well as the N-terminal nonapeptide Tat(1-9) and other peptides containing the N-terminal sequence XXP, also inhibit DP IV and therefore T cell activation. Studying the effect of amino acid exchanges in the N-terminal three positions of the Tat(1-9) sequence, we found that trypt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
35
0
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 50 publications
0
35
0
1
Order By: Relevance
“…In contrast, recent reports found elevated numbers of CD26 ϩ CD4 ϩ T cells in peripheral blood and cerebrospinal fluid from patients with multiple sclerosis (MS), and suggested that CD26/DP IV mediates T cell recruitment to airways in a rat asthma model (12)(13)(14)(15)(16)(17)(18). Moreover, in vitro and in vivo studies conducted with potent synthetic inhibitors identified CD26/DP IV as a target for immunosuppressive therapy (4,19,20). Due to their suppression of leukocyte functions, synthetic inhibitors of CD26/DP IV demonstrated profound therapeutic effects in several animal models of human diseases, including rheumatoid arthritis, transplantation, and MS (6 -8, 21), but the underlying mechanisms are still elusive.…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…In contrast, recent reports found elevated numbers of CD26 ϩ CD4 ϩ T cells in peripheral blood and cerebrospinal fluid from patients with multiple sclerosis (MS), and suggested that CD26/DP IV mediates T cell recruitment to airways in a rat asthma model (12)(13)(14)(15)(16)(17)(18). Moreover, in vitro and in vivo studies conducted with potent synthetic inhibitors identified CD26/DP IV as a target for immunosuppressive therapy (4,19,20). Due to their suppression of leukocyte functions, synthetic inhibitors of CD26/DP IV demonstrated profound therapeutic effects in several animal models of human diseases, including rheumatoid arthritis, transplantation, and MS (6 -8, 21), but the underlying mechanisms are still elusive.…”
mentioning
confidence: 76%
“…Specifically, we tested the hypothesis that the CD26 molecule plays a critical regulatory role in autoimmune disease by serving as a target for naturally occurring inhibitory ligands that were previously identified, including ubiquitously expressed proteins such as the thromboxane A2 receptor (TXA2-R) (3,4,19,24). By demonstrating systemic deregulation of Th1 immune responses and exacerbation of EAE in mice lacking CD26/DP IV, we provide evidence for a nonredundant role of this molecule as a negative regulator of T cell functions during inflammatory immune responses in vivo.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As with GLP-1 degradation, this is due mainly to rapid cleavage by a highly specific aminopeptidase, dipeptidyl peptidase IV (DPP IV; EC.3.4.14.5) a member of the prolyl oligopeptidase family of serine proteases [17]. DPP IV is expressed ubiquitously in mammalian tissues and organs [18] with a specificity for removing dipeptides from the amino terminus of a wide range of peptides with penultimate proline, alanine and hydroxyproline residues [19,20]. DPP IV is in close contact with hormones circulating in the blood, located on endothelial cells of the blood vessels and, moreover, it is found as a soluble enzyme in blood plasma [21].…”
mentioning
confidence: 99%